Self-Esteem Pasien Gagal Ginjal Kronis di Unit Hemodialisis RSUD Welas Asih Jawa Barat - Afina Chairunnisa; Maria Komariah; Eka Afrima Sari (Malahayati Nursing Journal, 2026)
ABSTRACT Patients with chronic kidney disease (CKD) undergoing hemodialysis face not only physical burdens, but also psychological, social, and spiritual challenges. One of the psychological impacts often experienced is a decline in self-esteem due to dependence on dialysis machines, changes in body image, and limitations on social activities. Low self-esteem can affect compliance with therapy and impact the patient's quality of life. This study aims to determine the level of self-esteem in CKD patients undergoing hemodialysis at Welas Asih Regional General Hospital in West Java. This study uses a quantitative descriptive design with a cross-sectional approach. The data used were secondary data from a study by lecturers at the Faculty of Nursing, Padjadjaran University, entitled “Harmony in Health: The Intersection of Natural Resources and Well-Being,” which was conducted in September–October 2024. The research instrument used was the Rosenberg Self-Esteem Scale (RSES) and was analyzed using univariate analysis. The results showed that most CKD patients undergoing hemodialysis were in the low self-esteem category (66.67%). Low self-esteem was more prevalent among female respondents, those who were married, had a secondary education, were unemployed, had undergone hemodialysis for ≥12 months, and had a history of comorbidities such as hypertension. This study indicates that low self-esteem remains a prominent psychological issue among CKD patients undergoing hemodialysis at Welas Asih Regional General Hospital in West Java. These findings emphasize the importance of addressing psychological aspects as part of nursing care, particularly in supporting patients' self-acceptance and adaptation to chronic illness. Keywords: Chronic Kidney Disease, Hemodialysis, Self-Esteem.  ABSTRAK Pasien gagal ginjal kronis (GGK) yang menjalani hemodialisis tidak hanya menghadapi beban fisik, tetapi juga tantangan psikologis, sosial, dan spiritual. Salah satu dampak psikologis yang sering dialami adalah penurunan self-esteem akibat ketergantungan pada mesin dialisis, perubahan citra tubuh, serta keterbatasan aktivitas sosial. Rendahnya self-esteem dapat memengaruhi kepatuhan terhadap terapi dan berdampak pada kualitas hidup pasien.  Penelitian ini bertujuan untuk mengetahui gambaran tingkat self-esteem pada pasien GGK yang menjalani hemodialisis di RSUD Welas Asih Jawa Barat. Penelitian ini menggunakan desain deskriptif kuantitatif dengan pendekatan cross-sectional. Data yang digunakan merupakan data sekunder dari penelitian dosen Fakultas Keperawatan Universitas Padjadjaran dengan judul “Harmony in Health: The Intersection of Natural Resources and Well-Being” yang dilaksanakan pada bulan September–Oktober 2024. Instrumen penelitian yang digunakan adalah Rosenberg Self-Esteem Scale (RSES) dan dianalisis menggunakan analisis univariat. Hasil penelitian menunjukkan bahwa sebagian besar pasien GGK yang menjalani hemodialisis berada pada kategori self- esteem rendah (66.67%).Self-esteem rendah lebih banyak ditemukan pada responden perempuan, menikah, tingkat pendidikan menengah,tidak bekerja, yang menjalani hemodialisis ≥12 bulan, serta dengan riwayat penyakit penyerta seperti hipertensi.Penelitian ini menunjukkan bahwa self-esteem rendah masih menjadi masalah psikologis yang menonjol pada pasienGGK yang menjalani hemodialisis di RSUD Welas Asih Jawa Barat. Temuan ini menegaskan pentingnya perhatian terhadap aspek psikologis sebagai bagian dari asuhan keperawatan, khususnya dalam mendukung penerimaan diri dan adaptasi pasien terhadap penyakit kronik Kata Kunci: Gagal Ginjal Kronis, Hemodialisis, Self-Esteem.